Quantitative Ultrashort Echo Time Magnetic Resonance Imaging Evaluation of Postoperative Menisci: a Pilot Study - Sneag, Darryl B. (HSS J, 2014)
BACKGROUND: Magnetic resonance imaging (MRI) visualization of meniscal signal is particularly challenging as the highly organized ultrastructure of meniscal fibrocartilage yields very short T2 values (∼6 ms) and a paucity of signal intensity during conventional image acquisition. QUESTION/PURPOSE: The purpose of this study was to evaluate the feasibility of imaging postoperative menisci using an experimental, quantitative ultrashort echo time (UTE) MRI pulse sequence. This sequence acquires short echo images (echo time (TE) ∼0.3 ms) to produce multi-echo images for quantitative T2* calculations that provide an objective measure of collagen organization. PATIENTS AND METHODS: MRI scans of the knee were acquired at 6- and 12-month intervals on a clinical 3.0 T scanner following meniscal surgery in eight patients (ages 13–41), four of whom underwent repair and the other four partial meniscectomy. Conventional MRI sequences were qualitatively evaluated for meniscal morphology and signal and correlated with quantitative UTE results. RESULTS: A wide range of mean T2* values for both postsurgical groups was measured, and these values changed for each patient between the 6- and 12-month intervals. In many instances, the UTE sequence demonstrated quantitative differences between the two time intervals that were not detected with conventional sequences. CONCLUSIONS: This pilot study presents preliminary, observational data to be used as a baseline for future studies. Although the T2* values did not reveal a trend in either group or correlate with expected signal changes on conventional MRI, we speculate that the UTE sequence may detect ultrastructural alterations in meniscal composition that are otherwise not perceived with routine fast spin echo (FSE) sequences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11420-014-9420-x) contains supplementary material, which is available to authorized users.